Емпіричне дослідження особливостей соціального та психологічного благополуччя вимушених переселенців - Медведєва, О. В.; Medvedieva, O. V.; ORCID: https://orcid.org/ 0000-0003-4445-7355 (Габітус. - 2023. - Вип. 46. - С. 188-192, 2023)
Наведено результати емпіричного дослідження соціального та психологічного благополуччя вимушених переселенців. Зазначено, що внутрішньо переміщені особи є однією з особливо уразливих категорій населення. Досвід переміщення стає для них травматичною подією, яка призводить до радикальних трансформацій у сімейному, економічному, соціальному, культурному житті й позначається на благополуччі. Презентовано результати теоретичного аналізу проблеми благополуччя особистості у сучасній психології. Вибірку становили жінки та чоловіки, які мають статус внутрішньо переміщених осіб.

The article presents the results of an empirical study of the social and psychological well-being of forced migrants. The relevance of the study is substantiated. It is noted that internally displaced persons (IDPs) are one of the particularly vulnerable categories of the population. The experience of displacement becomes a traumatic event for them, which leads to radical transformations in family, economic, social, cultural life and affects the well-being of forcibly displaced people. The results of the theoretical analysis of the problem of personal well-being in modern psychology are presented. The sample consisted of women and men who have the status of internally displaced persons (IDPs). The first group included women (163 people), the second group consisted of men (91 people). Psychodiagnostic tools: questionnaires "Express assessment of psychological well-being" by K. Riff, adapted by N. Shishko, and "Scale of social well-being" by K. Keys, interpreted by A. Chetveryk-Burchak. An empirical study of the social and psychological well-being of women and men who have the status of internally displaced persons revealed the peculiarity of the functioning of the investigated phenomena in these groups. In female IDPs, such components of social well-being as social acceptance and social actualization are more pronounced, in men – coherence with society. Among the components of psychological well-being, positive relationships with others turned out to be more characteristic for women, while for men – personal growth. Therefore, the key to maintaining social and psychological well-being in women is a positive attitude towards society, mediated by a positive attitude and trust in individual people, interaction with whom is characterized by depth and comfort, confidence in their potential, which motivates them to accept collective responsibility and social activity. Men are characterized by greater realism in assessing social life, greater interest in understanding the peculiarities of its functioning, meaningful analysis of existing life experience and acquisition of new ones, orientation towards the realization of one's own potential, self-improvement.

Приведены результаты эмпирического исследования социального и психологического благополучия вынужденных переселенцев. Отмечено, что внутренне перемещенные лица являются одной из особо уязвимых категорий населения. Опыт перемещения становится для них травматическим событием, которое приводит к радикальным трансформациям в семейной, экономической, социальной, культурной жизни и сказывается на благополучии. Представлены результаты теоретического анализа проблемы благополучия личности в современной психологии. Выборку составляли женщины и мужчины, имеющие статус внутренне перемещенных лиц.
Empirical study of the features of the social and psychological well-being of forced migrants
Медведєва, О. В. Емпіричне дослідження особливостей соціального та психологічного благополуччя вимушених переселенців / Медведєва О. В. // Габітус. - 2023. - Вип. 46. - С. 188-192. - DOI: https://doi.org/10.32782/2663-5208. 2023.46.30.
Keywords: Психологія. Рsychology. Психология; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; вимушені переселенці; forced migrants; вынужденные переселенцы; внутрішньо переміщені особи; internally displaced persons; внутренне перемещенные лица; гендер; gender; психологічне благополуччя; psychological well-being; психологическое благополучие; соціальне благополуччя; social welfare; социальное благополучие